Analysis Of KKGO Muncar Athlete Achievement Based on Physical Condition Level and Anthropometry - Arya T Candra; Galih Farhanto (IKIP Budi Utomo Malang, 2021)
Achieving an optimal performance is one way for athletes to demonstrate the ability and quality of performance in a sport. Physical condition is the coverage of several indicators related to human physical abilities which directly contribute to the physical activity ability of an athlete. In addition, anthropometry is also a determining factor for the success of athletes in achieving an achievement. The purpose of this study was to determine and provide evidence in the form of scientific data from the results of research related to the physical condition and anthropometry levels of athletes, because these 2 indicators greatly influence the achievement of athletes. This type of research is descriptive quantitative, using a survey method with test and measurement instruments. The samples in this study were 10 volleyball athletes and 10 athletic athletes aged 9-12 years. The results of data analysis based on the results of the study indicate that the problem of minimal achievement of athletes in volleyball and athletics is due to the level of physical condition and anthropometry which are still less than ideal.